Sugar-modified G-quadruplexes : effects of LNA-, 2'F-RNA- and 2'F-ANA-guanosine chemistries on G-quadruplex structure and stability - Phan, Anh Tuân (2014)
G-quadruplex-forming oligonucleotides containing modified nucleotide chemistries have demonstrated promising pharmaceutical potential. In this work, we systematically investigate the effects of sugar-modified guanosines on the structure and stability of a (4+0) parallel and a (3+1) hybrid G-quadruplex using over 60 modified sequences containing a single-position substitution of 2′-O-4′-C-methylene-guanosine (LNAG), 2′-deoxy-2′-fluoro-riboguanosine (FG) or 2′-deoxy-2′-fluoro-arabinoguanosine (FANAG). Our results are summarized in two parts: (I) Generally, LNAG substitutions into ‘anti’ position guanines within a guanine-tetrad lead to a more stable G-quadruplex, while substitutions into ‘syn’ positions disrupt the native G-quadruplex conformation. However, some interesting exceptions to this trend are observed. We discover that a LNAG modification upstream of a short propeller loop hinders G-quadruplex formation. (II) A single substitution of either FG or FANAG into a ‘syn’ position is powerful enough to perturb the (3+1) G-quadruplex. Substitution of either FG or FANAG into any ‘anti’ position is well tolerated in the two G-quadruplex scaffolds. FANAG substitutions to ‘anti’ positions are better tolerated than their FG counterparts. In both scaffolds, FANAG substitutions to the central tetrad layer are observed to be the most stabilizing. The observations reported herein on the effects of LNAG, FG and FANAG modifications on G-quadruplex structure and stability will enable the future design of pharmaceutically relevant oligonucleotides.